Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd001863.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Education for contraceptive use by women after childbirth

Abstract: Analysis 2.1. Comparison 2 Contraceptive information (one time): physician counseling versus video versus pamphlet, Outcome 1 Satisfied with 'counseling' after the session: video versus physician. . . . . . . . . . . . Analysis 2.2. Comparison 2 Contraceptive information (one time): physician counseling versus video versus pamphlet, Outcome 2 Satisfied with 'counseling' after the session: video versus written information. . . . . . . . . Analysis 3.1. Comparison 3 Contraceptive counseling (one time) versus no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…Planners aligned strategies with target increases in service coverage. Target setting was based on past demonstrated achievements in coverage in the country and local expertise as global literature shows no consistent patterns in the coverage levels attained by various strategies [29-31] and context and implementation are heavily influential [32,33]. To improve reliability, a ceiling was set for projected met need in line with the highest achievement of the region in which the study site was placed (based on Demographic Health Survey (DHS) data) to avoid excessively optimistic estimates by local planners.…”
Section: Methodsmentioning
confidence: 99%
“…Planners aligned strategies with target increases in service coverage. Target setting was based on past demonstrated achievements in coverage in the country and local expertise as global literature shows no consistent patterns in the coverage levels attained by various strategies [29-31] and context and implementation are heavily influential [32,33]. To improve reliability, a ceiling was set for projected met need in line with the highest achievement of the region in which the study site was placed (based on Demographic Health Survey (DHS) data) to avoid excessively optimistic estimates by local planners.…”
Section: Methodsmentioning
confidence: 99%
“…Limited evidence suggests that some educational interventions can increase uptake of contraception-including the most effective methods-after childbirth. 45,46 In Scotland, information given by midwives at an antenatal visit has been part of the pathway of a successful initiative to increase LARC uptake after delivery. 47 Peri-abortion information-giving alone does not appear to influence uptake of LARC or risk of further unplanned pregnancy; 48 it should be part of a pathway to facilitate access to and initiation of contraception.…”
Section: Lessons For Improving Provision Of Contraception After Prementioning
confidence: 99%
“…Provider proficiency in carrying out comprehensive education and counseling on postpartum contraception is particularly important in settings where literacy rates are low [12]. In a systematic review, Lopez et al [13] indicated that education on postpartum contraceptive use is associated with increased contraception use and a reduction in the occurrence of unplanned pregnancies. They further found that both short-term and multiple-contact educational interventions had positive effects on rates of postpartum contraceptive use [13].…”
Section: Introductionmentioning
confidence: 99%